2003
DOI: 10.1021/ma034381n
|View full text |Cite
|
Sign up to set email alerts
|

Degradation Mechanism and Kinetics of Thermosensitive Polyacrylamides Containing Lactic Acid Side Chains

Abstract: Diblock copolymers of poly(N-isopropylacrylamide-co-N-(2-hydroxypropyl)methacrylamide lactate) (poly(NIPAAm-co-HPMAm-lactate)) as a thermosensitive block and poly(ethylene glycol) (PEG) as a hydrophilic block form polymeric micelles above the cloud point (CP) of the temperature-sensitive block. Destabilization of these micelles occurs upon hydrolysis of the lactate side chains. Here we report on the degradation kinetics of the HPMAm-mono(di)lactate monomers and their copolymers with NIPAAm. The degradation of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
143
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(157 citation statements)
references
References 40 publications
13
143
0
Order By: Relevance
“…The degradation mechanism of p(HPMAm-lac)-PEG-based hydrogels is due to hydrolysis of the numerous ester bonds present in the polymer networks, as described earlier. 37,41 It was shown that the lactate side chains of p(HPMAm-lac) with a free terminal OH group are hydrolyzed in approximately 1 week. The terminal lactate moiety in the HPMAm-dilactate is degraded faster than the one in the HPMAm-monolactate, because by a nucleophilic attack of the hydroxy terminus, the ester bond that is located two lactate units further on in the side chain is hydrolyzed in a so-called backbiting mechanism.…”
Section: Resultsmentioning
confidence: 99%
“…The degradation mechanism of p(HPMAm-lac)-PEG-based hydrogels is due to hydrolysis of the numerous ester bonds present in the polymer networks, as described earlier. 37,41 It was shown that the lactate side chains of p(HPMAm-lac) with a free terminal OH group are hydrolyzed in approximately 1 week. The terminal lactate moiety in the HPMAm-dilactate is degraded faster than the one in the HPMAm-monolactate, because by a nucleophilic attack of the hydroxy terminus, the ester bond that is located two lactate units further on in the side chain is hydrolyzed in a so-called backbiting mechanism.…”
Section: Resultsmentioning
confidence: 99%
“…The PEG 2 -ABCPA macroinitiators with PEG 2000, PEG 5000 and PEG 10 000 were prepared as described previously [34]. HPMA-dilactate was obtained as reported by Neradovic et al [38].…”
Section: Methodsmentioning
confidence: 99%
“…The size (Z ave ) and light scattering intensity (LSI) of the micelles were monitored by DLS while cooling a micellar suspension from 25 to 2 °C in 90 min. [15] Hydrolytic stability was analyzed by monitoring the Z ave and the LSI of the micelles with DLS under accelerated hydrolytic conditions (pH 10.0 and 37 °C) for 22 h. [16,47,48] The pH of the micellar dispersion was adjusted to pH 10.0 by diluting the micellar dispersion 5-fold with 500 mM Na 2 CO 3 /NaHCO 3 pH 10.0 buffer. The integrity of the CCPM against the dissolution by DMF was performed and also to examine the amount of non-crosslinked free polymer chains in the CCPM dispersion.…”
Section: Stability and Reduction-sensitive De-crosslinking Of The Ccpmmentioning
confidence: 99%
“…This value is in line with other published papers, in which the target site accumulation of micelles (as well as other nanocarriers) was evaluated using optical and radionuclide-based imaging techniques. [28,[43][44][45][46][47][48] Figure 5C also provides feedback on the accumulation of the iCCPM in several different healthy tissues. The liver uptake of the iCCPM was found to be ~20% at 48 h p.i., which corresponds with previous reports, and results from clearance by the mononuclear phagocytic system (MPS).…”
Section: In Vivo Optical Imaging Of the Biodistribution And Tumor Accmentioning
confidence: 99%